Patterns of Attack: Understanding Al Qaeda in the Islamic Maghreb. - Zapata, Mollie E. (Tufts Archival Research Center, 2015)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: To give a complete picture of AQIM, this paper will begin with a brief history of the evolution of Islamic extremism in Algeria and an overview of AQIM today, focusing on five categories of analysis and drawing on data about regional terrorist incidents, to assess recent change over time: ideology, leadership, organizational structure, locus of operations, targeting, and ties with other groups. I use Analysis of Competing Hypothesis (ACH) to test whether AQIM is more of a national or international threat based on its locus of operations and targeting. Insights derived from this quantitative and qualitative analysis will show that AQIM is an internationally oriented movement, influenced by the tactics of Al Qaeda, but that the group's ability to operate outside of its current geographic area is severely limited and it is essentially in "survival mode." I use Social Networks Analysis (SNA) to assess and visualize the group's current ties with other Islamist groups (within Africa and internationally) to show that all AQIM's former African affiliates are now aligned with ISIS, which will likely be an influencing factor in AQIM's calculus of whether or not they should remain loyal to Al Qaeda. The historical analysis, combined with the data on AQIM's more recent activities, illuminates a cyclical pattern, now midway through its third rotation, of Islamists going abroad to fight the jihad then returning to Algeria with new skills, increasingly extreme ideology, and international ties. Understanding this pattern will point to projections for the group's future.